The Style of Farokhi Yazdi’s poem - عبدالله حسن زاده میرعلی; سیده زهره نصیری سلوش (تاریخ ادبیات)
Mashroteh movement, by making fundamental changes in political, social and cultural and literature changed the Qajar period. The factors such as the relationship with the West, itineraries, establishment of new schools, translated Western books and press provided modernity in Iranian people. This modernity affected on the poem poetry and prose of Mashroteh period. Since the study of stylistic is considered as the important methods of the analysis of literary works, this paper attempt to analyze Farokhi Yazdi’s poems in the tree levels of linguistics, literary and intellectual. In analysis of whole contain of the poems and in considering in linguistics and literary 50% of the poems; sporadically from first, mid and end of the anthology. In linguistics and literary part, amount of use of those cases mentioned by taking the examples and at the end a final analysis of the relationship of language and literary properties with poet’s thoughts presented.Finall to show the more accurate linguistic and literary properties several figures have been provided.